Usage of eHealth/mHealth Services among Young Czech Adults and the Impact of COVID-19: An Explorative Survey - Dolezel, Michal; Smutny, Zdenek (International journal of environmental research and public health, 2021)
Various mHealth/eHealth services play an increasingly important role in healthcare systems and personal lifestyle management. Yet, the relative popularity of these services among the young population of the Czech Republic was not known. Therefore, we carried out an on-line survey with a convenience sample (n = 299) of young adults aged 18-29 and living in the Czech Republic. To this end, we adapted the survey instrument which was previously used in a similar study conducted in a different cultural context (Hong Kong). In our study, we found out that health tutorial activities (i.e., acquiring information on diet, exercise, fitness) were the most common among our respondents (M = 2.81, SD = 1.14). These were followed by health information seeking activities (i.e., acquiring information on medical problems) (M = 2.63, SD = 0.89) and medical services (i.e., the eHealth/mHealth services that provide infrastructural support, such as ePrescription and doctor appointment organizers) (M = 2.18, SD = 0.97). Based on the grouping according to gender and existing health condition, pairwise comparisons showed statistically significant differences. We also briefly analyzed the influence of the COVID-19 pandemic on the examined activities. Based on their relative popularity, we suggest leveraging the potential of health tutorial activities to improve public health.
Keywords: Young Adult; personal health informatics; mladý dospělý; mHealth apps; Česká republika; consumer health information; pandemie; průzkumy a dotazníky; SARS-CoV-2; Czech Republic; Telemedicine; lidé; Humans; telemedicína; consumer health data; self-tracking; Pandemics; Hong Kong; Surveys and Questionnaires; Hongkong; quantified self; COVID-19